Hydrothermal synthesis of Bi2MoO6visible-light-driven photocatalyst - Anukorn Phuruangrat (2018)
© 2015 Anukorn Phuruangrat et al. Bismuth molybdate (Bi2MoO6) nanoplates were synthesized by the hydrothermal reaction of bismuth nitrate and sodium molybdate as starting materials at 120-180°C for 5-20 h. X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, and scanning electron microscopy (SEM) were used to investigate the effect of reaction temperature and length of reaction time on phase and morphologies of the as-synthesized Bi2MoO6samples. In this research, orthorhombic well-crystallized Bi2MoO6nanoplates with the presence of stretching and bending vibrations of MoO6and BiO6octahedrons were detected, and the Bi2MoO6nanoplates synthesized at 180°C for 5 h exhibit the highest photocatalytic efficiency over 96% within 100 min visible-light irradiation.